Transborder Crisis and Security Implications for West African Sub-Region - Dominic Aondona Iornumbe; Tanko Shawulu Paul; Sani Inusa Milala (Jurnal Restorasi : Hukum dan Politik, 2025)
The transborder crisis in West Africa has had far-reaching implications for the region’s security. According to a report by the United Nations, the region is facing “unprecedented levels of security and humanitarian challenges”. The crisis has been fueled by the activities of non-state actors such as violent extremists, criminal networks, and armed groups. These groups have forced the closure of thousands of schools and health centers, leaving millions of children without access to education and healthcare. The situation has been further compounded by the impact of climate change and food insecurity, which has led to socio-political instability in the region. Countries along the coast of the Gulf of Guinea have also seen an increase in attacks against their territories, threatening transport routes to landlocked nations further north. Despite these challenges, West Africa and the Sahel still present immense opportunities. The United Nations Office for West Africa and the Sahel (UNOWAS) has urged ambassadors to continue supporting a strategy centered on building resilience, promoting good governance, and strengthening peace and security. UNOWAS has also been working with other UN entities to contribute to conflict resolution at both regional and local levels. The research used secondary data. Collective security theory was adopted. The research recommends cooperation among members states to overcome challenges of transborder security.